Consumer flexibility, data quality and location choice - Irina Baye; Irina Hasnas (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2014)
We analyze firms' location choices in a Hotelling model with two-dimensional consumer heterogeneity, along addresses and transport cost parameters (flexibility). Firms can price discriminate based on perfect data on consumer addresses and (possibly) imperfect data on consumer flexibility. We show that firms' location choices depend on how strongly consumers differ in flexibility. Precisely, when consumers are relatively homogeneous, equilibrium locations are socially optimal regardless of the quality of customer flexibility data. However, when consumers are relatively differentiated, firms make socially optimal location choices only when customer flexibility data is perfect. These results are driven by the optimal strategy of a firm on its turf, monopolization or market-sharing, which in turn depends on consumer heterogeneity in flexibility. Our analysis is motivated by the availability of customer data, which allows firms to practice third-degree price discrimination based on both consumer characteristics relevant in spatial competition, addresses and transport cost parameters.
Keywords: D43; L13; R30; R32; 330; Location Choice; Price Discrimination; Customer Data